Are liquid biopsies a surrogate for tissue EGFR testing?. (15th February 2018) - Goldman, J W; Noor, Z S; Remon, J; Besse, B; Rosenfeld, N
Abstract: Molecular profiling has changed the treatment landscape in advanced non-small-cell lung cancer. Accurately identifying the tumours that harbour sensitizing EGFR mutations, the most common targetable molecular alteration, as well as those with acquired resistance mutations (e.g. T790M ) on treatment is a high clinical priority. The current clinical gold standard is genotyping of tumour specimens. However, the practical utility of this approach is limited by the lack of available tissue and the potential complications associated with biopsies. With the advent of newer sequencing assays, it has become feasible to assess tumour genomics via a blood sample, termed a 'liquid biopsy'. In this review, we summarize the available techniques for liquid biopsies and their applicability for detecting sensitizing and resistance EGFR mutations and how these results may be used for making treatment decisions.